Cost-Effectiveness of Ferrous Fumarate–Folic Acid and Ferrous Gluconate–Multivitamins in a High Prevalence Area of Iron Deficiency Anemia in Indonesia - Rakanita Y; Syamsunarno MRAA; Sinuraya RK; Suradji EW; Abdulah R; Suwantika AA (Dove Medical Press, 2021)
Yasinta Rakanita,1,2 Mas Rizky AA Syamsunarno,3 Rano K Sinuraya,1,4 Eka W Suradji,5,6 Rizky Abdulah,1,4 Auliya A Suwantika1,4,7 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 2College of Pharmaceutical Sciences Pelita Mas, Palu, Indonesia; 3Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 4Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, Indonesia; 5Department of Public Health, Faculty of Medicine, Krida Wacana University, Jakarta, Indonesia; 6UKRIDA Hospital, Jakarta, Indonesia; 7Center for Health Technology Assessment, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Auliya A SuwantikaDepartment of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, IndonesiaEmail auliya@unpad.ac.idBackground: Up to now, the combinations of ferrous fumarate-folic acid (FF-FA) and ferrous gluconate-multivitamins (FG-MV) have been implemented by the local government in the province of Papua. Nevertheless, there is no a specific economic evaluation that has been applied to investigate the cost-effectiveness of FF-FA and FG-MV.Objective: This study aimed to investigate the cost-effectiveness of FF-FA and FG-MV to be implemented in Teluk Bintuni, as one of the districts with the highest prevalence of iron deficiency anemia in Papua by taking the healthcare perspective into account.Methods: A prospective observational study was applied by considering two groups of women (15- 49 years old) with iron deficiency anemia who received FF-FA and FG-MV from September to November 2018. Applying a purposive sampling method, respondents were selected from 875 targeted women in six sub-districts, who met inclusion criteria. To estimate the total cost, we applied a healthcare perspective that considered direct medical cost only (eg, the procurement cost of iron tablets, cost of Hb test, and cost of healthcare visit). To estimate the effectiveness of intervention, we applied two major parameters, such as Hb level and utility score in quality-adjusted life year (QALY). The cost-effectiveness values were evaluated by using the criteria on the cost-effectiveness of healthcare intervention according to the threshold of gross domestic product (GDP) per capita (cost per QALY gained).Results: From 875 targeted women in six sub-districts who met inclusion criteria, we found approximately 222 women with moderate-severe iron deficiency anemia and 110 women with complete data in the group of FF-FA (n=69) and FG-MV (n-41). The results showed that there were significant differences (p-value < 0.05) on the number of respondents, age, oral iron cost, total healthcare cost and utility score in both intervention groups. Comparing the use of FG-MV with FF-FA, we estimated the incremental cost-effectiveness ratios (ICERs) would be $255.77 per controlled patient, $142.09 per patient with Hb increment > 2.00 g/dL, $79.93 per patient with Hb increment > 1.00 g/dL, and $11.59 per QALY gained.Conclusion: The ICER was estimated to be $11.59 per QALY gained, which was highly cost-effective, according to GDP-based cost-effectiveness threshold. In addition, the utility score of women with iron deficiency anemia was considered to be the most influential factor impacting the cost-effectiveness value.Keywords: ICER, cost per controlled patient, cost per patient with Hb increment > 2.00 g/dL, cost per patient with Hb increment > 1.00 g/dL, cost per QALY gained